A search for doxycycline-dependent mutations that increase Drosophila melanogaster life span identifies the VhaSFD, Sugar baby, filamin, fwd and Cctl genes. - Landis, G.N.; Bhole, D.; Tower, J. (Genome Biology, 2003)
A P-type transposable element called PdL has been engineered with a doxycycline-inducible promoter directed out through the 3' end of the element. Insertion of PdL near the 5' end of a gene often yields doxycycline-dependent overexpression of that gene and a mutant phenotype. This functional genomics strategy allows for efficient screening of large numbers of genes for overexpression phenotypes.PdL was mobilized to around 10,000 new locations in the Drosophila melanogaster genome and used to search for genes that would extend life span when overexpressed. Six lines were identified in which there was a 5-17% increase in life span in the presence of doxyxcycline. The mutations were molecularly characterized and in each case a gene was found to be overexpressed using northern blots. Two genes did not have previously known phenotypes and are implicated in membrane transport: VhaSFD encodes a regulatory subunit of the vacuolar ATPase proton pump (H+-ATPase), whereas Sugar baby (Sug) is related to a maltose permease from Bacillus. Three PdL mutations identified previously characterized genes: filamin encodes the homolog of an actin-polymerizing protein that interacts with presenilins. four wheel drive (fwd) encodes a phosphatidylinositol-4-kinase (PI 4-kinase) and CTP:phosphocholine cytidylyltransferase-l (Cctl) encodes the rate-limiting enzyme in phosphatidylcholine synthesis. Finally, an apparently novel gene (Red herring, Rdh) was found in the first intron of the encore gene.Screening for conditional mutations that increase Drosophila life span has identified genes implicated in membrane transport, phospholipid metabolism and signaling, and actin cytoskeleton organization.